2012
DOI: 10.1111/j.1442-2042.2011.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

New clinical evidence of silodosin, an α1A selective adrenoceptor antagonist, in the treatment for lower urinary tract symptoms

Abstract: Abbreviations & Acronyms a1-AR = a1-adrenoceptor a1A-AR = a1A-adrenoceptor AE = adverse effects BOO = bladder outlet obstruction BOOI = bladder outlet obstruction index BPH = benign prostatic hyperplasia CI = confidence interval CP/CPPS = chronic prostatitis/chronic pelvic pain syndrome DE = disorders of ejaculation GRA = global response assessment HR-QOL = health-related quality of life IPSS = International Prostate Symptom Score ITT = intention to treat LOCF = last observation carried forward LUTS = lower ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
1
16
1
Order By: Relevance
“…These adverse reactions were considered attributable to the pharmacological actions of these α 1 ‐receptor blockers themselves. In concordance with this observation, the previous study also showed more frequent occurrence of ejaculation disorder in patients treated with silodosin (which has a very high affinity to the α 1A receptor) than in untreated patients; however, the ages of the patients enrolled in the present study were not in the range where their sexual function was of concern.…”
Section: Discussionsupporting
confidence: 90%
“…These adverse reactions were considered attributable to the pharmacological actions of these α 1 ‐receptor blockers themselves. In concordance with this observation, the previous study also showed more frequent occurrence of ejaculation disorder in patients treated with silodosin (which has a very high affinity to the α 1A receptor) than in untreated patients; however, the ages of the patients enrolled in the present study were not in the range where their sexual function was of concern.…”
Section: Discussionsupporting
confidence: 90%
“…BPH is a common enlargement of the prostate gland that can lead to bladder outlet obstruction, LUTS and impaired quality of life. BPH is present in 50% of men aged older than 50 years, and in approximately 90% of those over the age of 80 years . BPH is a progressive condition.…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of tamuslosin hydrochloride to α1A receptor is comparatively high while naftopidil is characterized to have comparatively high affinity to α1D receptor subtype [3,4]. On the other hand, silodosin acts on α1A receptor in a very specific manner [5]. The practical clinical application of silodosin started in Japan in 2006.…”
Section: Introductionmentioning
confidence: 99%